Psychosocial aspects of disability [ insider perspectives and counseling strategies - Marini, Irmo; Glover-Graf, Noreen M.; Millington, Michael Jay (Springer Publishing, 2012)
What a marvelous and amazing textbook. Drs. Marini, Glover-Graf and Millington have done a remarkable job in the design of this highly unique book, that comprehensively and very thoughtfully addresses the psychosocial aspects of the disability experience. These highly respected scholars have produced a major work that will be a central text in rehabilitation education for years to come.